KYAI DAN ISLAM DALAM MEMPENGARUHI PERILAKU MEMILIH MASYARAKAT KOTA TASIKMALAYA - Nasir, Nurlatipah (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2015)
Huntington claimed that political participation is a concept that unknown in Islamic societis. Indonesia proved that Huntington was wrong, as the largest mulim country in the world, the participation level in general election is quite high.As a studi case, Tasikmalaya even more unique, while the Islamic partyin some places experiencing the trend of declining votes, then in Tasikmalaya remained stable. The stability of the Islamic Party in Tasikmalaya is supported by various factors, especially by the role of Kyai, the leader of muslim societies.